The amazonian indigenous writing: native communication to think about current issues (Research, Society and Development, 2022)
The aims was to describe the communication practices of indigenous writers from the Wewa'a Institute, headquartered in Manaus/AM, northern region of Brazil, to disseminate their works and their ancestral knowledge and knowledge. In the theoretical framework discussed, we emphasize the identification of authors who deal with ethnomedialogy and native literature, as well as who it is intended for and how the content produced is delimited. The research was qualitative and transversal, observing implications that are serving as sets of strategies for the Wewa'a Institute to project visibilities in the Amazon and national context. Discussions were held regarding kinship formations and ancestral conceptions that influence this literature, which is actually an Amazonian, native, cosmological literature. In the writings, there is debate about the relevance attributed to a mythical or living being, who is believed to be a “father/guide”, guiding clan unions, following a line that focuses on the formation of the narrative. Therefore, we conclude that there are important informational and communicational biases to be considered in the context of Amazonian writing.